Analisis Sentimen Gambar pada Media Sosial dengan Pendekatan Deep Learning - T, Ronaldito Juan Bantaras; Raharja, Made Agung (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 3 (2023): JNATIA Vol. 1, No. 3, Mei 2023DO - 10.24843/JNATIA.2023.v01.i03.p22, 2023)
Sentiment analysis of images on social media using a deep learning approach is an interesting research topic in the field of artificial intelligence. It involves data collection, training deep neural network models, testing and evaluation, and application and analysis on social media. The results of this analysis provide valuable insights to users in understanding user responses to content, detecting evolving sentiment trends, and providing important insights for business purposes and decision-making. Deep learning offers a strong and effective method for understanding emotional expressions within images shared on social media  platforms.